Sense or sensibility—Ideological dilemmas in gamblers' notions of responsibilities for gambling problems - Samuelsson, Eva; Cisneros Örnberg, Jenny (Frontiers in Psychiatry, 2022)
The gambling market is a complex field of conflicting stakeholders and interests involving dimensions, such as economy, health, social inequality and morals. The division of responsibility between gamblers, the gambling industry and the regulating state for limiting the harmful effects of this activity, however, are unclear. The aim of this study was to explore how gamblers in the Swedish market attribute responsibility to various actors within the gambling field. Qualitative interviews were conducted with 37 gamblers experiencing extensive gambling problems. Based on a discourse analytical approach, five ideological dilemmas were identified, highlighting the tension between the, often contradictory, values that the participants need to relate to. On the individual level, the gamblers emphasize their own responsibility for their problem, thereby showing accountability in relation to themselves, their significant others and their peers as agents in recovery. On the corporate- and state levels however, the participants argue for a stronger public health approach, where the gambling companies should take further responsibility by living up to the legal regulations and where the state should ensure compliance and safeguard funding for treatment and research. The essential paradox between the individual responsibility discourse of self-regulation and the prevailing medical discourse of the gambler’s incapacity for self-control signifies an impossible equation that imposes feelings of guilt and shame upon an individual who is concurrently considered as both responsible and incapable. In order to reduce harm, the gambling industry must be more proactive with coercive external control measures to fulfil the duty of care they claim to adhere to, and the regulating state must ensure its compliance.